Barriers to the adoption of the internet and selection of e-commerce actions: Incidental motivations of micro-entrepreneurs - Gustavo Barrera Verdugo (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
For decades entrepreneurial motivations have been related to entrepreneurial behavior, in areas such as investments or formulation of strategies, however, its link with the adoption of e-commerce in microenterprises has not been explored in depth. Likewise, most of the research on e-commerce has been focused on studying small and medium-sized companies. Consequently, this research aims to assess the relationship of motivations of micro-entrepreneurs when developing their businesses, with the barriers they perceive to adopt the Internet, and the types of e-commerce activities they implement in their companies. In addition, demographic variables are analysed in order to facilitate the categorization of these organizations. Logistic regressions and Chisquare statistics are developed, on data published in the Fifth Micro-Entrepreneurship Survey of Chile. The results obtained show that the motivation for entrepreneurship based on family tradition is related to less Internet adoption and uses for e-commerce; also, it is evidenced that necessity and opportunity-based motivations are positively associated with Internet use for relationship purposes with clients and suppliers. This information is considered relevant in practical terms, since it allows strengthening the use of e-commerce in microenterprises, through the implementation of programs to support microentrepreneurs with incident characteristics, under the financing of governmental entities or private companies.
Keywords: L81; L86; L26; D91; 650; internet barriers; e-commerce uses; micro-enterprises; entrepreneurial motivations; demographic conditions